Mapeamento do município de Pires do Rio-GO: usando técnicas de geoprocessamento - Dias, Cristiane (2008)
This work had as objective to make the mapping of the Pires do Rio city of the environment, using techniques of geoprocessing, where it was carried through analyzes secular of the use of the land and covering vegetal of 1977, 2002 and 2007, and verified the mapped potentialities of categories. The Pires do Rio city of the Goiás is located between the geographic coordinates 17º 01' -17º 37' 28'' of South' 05' latitude and 48º 03' 21'' - 48º 42' 54'' of longitude West of Greenwich, occupying an area of 1073,369 Km2, with a population 26,857 in 2007. The materials used for accomplishment of this work had been to topographic leaves for elaboration of the limit and draining; digital leaf SE-22-X-D of the SIEG as base for the geology maps , geomorphologic and ground; leaf SE-22-X-D (MDE/SRTM) for maps of declivity, hydrographical sub-basins and hypsometry; images of satellites of the sensor ETM+/Landsat 7. For improvement of the limits of the categories of ground, geology and geomorphologic, update of the draining, mapping of the categories of use of the land and vegetal covering of 2002; MSS/Landsat 2 for construction of the use map land and vegetal covering of 1977; CCD/CBERS 2 for construction of the map of use land and vegetal covering of 2007 and of the farms. In Cartalinx software they had been digitalized the majority of the maps, except the maps of declivity, sub-basins, hypsometry and recommended use that had been elaborated in software IDRISI 32, which also carried through the crossings of the thematic maps. For construction of the map of the farms one typed the coordinates in the Excel was exported to Arcview 32, where the layout was become fulfilled. From the analysis of the results it is observed that the city is formed by 8 hydrographical subbasins, the greater is of the Ribeirão Brumado occupying 22% of the area; the category of geology predominant ´r Granada Gnaisse, Anfibolito, Quartzite in 45% of the total; how much to the relief of the city 37% little dissected presents the index; e altitude enters 700 800m, the dominant characteristic of declivity it is soft waved with interval of 3 8% in 47% of the total of the area; the types of predominant ground are the Cambissolos and Red Latossolo and occurring respectively, in 40% and 36% of the city. With the use of the images the following categories of use of the land had been identified (Ciliar Bush, Cerradão, Savana, Dirty Field, Clean Field, agriculture, pasture, reforestation, area of urban influence e, water bodies). The secular analysis of the use of the land proved that the pasture is the predominant category in these 30 years, occupying 47% of the city on average, and the natural vegetation had a significant reduction, mainly the dirty field in 55% of its area. How much to the map of recommended use, it was verified that 55% of the area recommended for agriculture and indicated 61% for the exotic reforestation are being busy with pasture. The geoprocessing techniques had facilitated the work of mapping of the city, the generated data make possible the identification of the ambient fragilities and suggestions to improve the use of the way land to guarantee its sustentability.